2020
DOI: 10.3390/nano10112130
|View full text |Cite
|
Sign up to set email alerts
|

New Nanostructured Carbon Coating Inhibits Bacterial Growth, but Does Not Influence on Animal Cells

Abstract: An electrospark technology has been developed for obtaining a colloidal solution containing nanosized amorphous carbon. The advantages of the technology are its low cost and high performance. The colloidal solution of nanosized carbon is highly stable. The coatings on its basis are nanostructured. They are characterized by high adhesion and hydrophobicity. It was found that the propagation of microorganisms on nanosized carbon coatings is significantly hindered. At the same time, eukaryotic animal cells grow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Microorganisms stained using a crystal violet indicator and examined under a microscope at 1000 magnification. The details of the experiment were described earlier [34]. Since we used a drop spectrophotometer (optical path length of about 50 µm) and microscopy, we reported the concentration of microorganisms in the number of bacteria per unit area.…”
Section: Bacteriostatic Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms stained using a crystal violet indicator and examined under a microscope at 1000 magnification. The details of the experiment were described earlier [34]. Since we used a drop spectrophotometer (optical path length of about 50 µm) and microscopy, we reported the concentration of microorganisms in the number of bacteria per unit area.…”
Section: Bacteriostatic Activity Assaymentioning
confidence: 99%
“…Human neuroblastoma SH-SY5Y and mouse primary dermal fibroblasts (Adult, C57BL/6) were cell cultures were used as standard cell models. SH-SY5Y cells in vitro can spontaneously intercontained between two phenotypes, neuroblast-like cells and epithelial-like cells [34]. The cells were grown in DMEM medium (Biolot, Moscow, Russia) supplemented with 10% fetal calf serum (Gibco, Waltham, MO, USA), 30 µg/mL gentamicin, at 37 • C and 5% carbon dioxide in a CO 2 incubator (Binder, Tuttlingen, Germany).…”
Section: Cell Culturementioning
confidence: 99%
“…For example, diamond-like carbon (DLC) nanofilm is a promising material for application in medical implants, with high mechanical and chemical inertness and biocompatibility [ 42 , 43 ]. Both cell culture and animal experiments have shown that DLC coating does not cause toxicity and inflammation [ 44 ]. The colloidal solution of nanocarbon has recently been shown to inhibit bacteria’s growth without affecting the viability of eukaryotic animal cells [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both cell culture and animal experiments have shown that DLC coating does not cause toxicity and inflammation [ 44 ]. The colloidal solution of nanocarbon has recently been shown to inhibit bacteria’s growth without affecting the viability of eukaryotic animal cells [ 44 ]. Studies by Jelinek et al have shown that Ge-doped DLC layers with low doping levels are not cytotoxic, while for higher doping levels, Ge has been proven to be cytotoxic, which is related to the production of reactive oxygen species [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coatings are considered as biocompatible with none or low cytotoxicity. For nanostructured carbon materials, such as graphene, fullerene and nanotubes, the picture is more complicated [7,8]. A weak property of the undoped DLC layers with a high sp 3 component is a relatively high internal stress resulting in a poor adhesion.…”
Section: Introductionmentioning
confidence: 99%